A hysteretic model considering Stribeck effect for small-scale magnetorheological damper. (8th May 2018) - Zhao, Yu-Liang; Xu, Zhao-Dong
Abstract: Magnetorheological (MR) damper is an ideal semi-active control device for vibration suppression. The mechanical properties of this type of devices show strong nonlinear characteristics, especially the performance of the small-scale dampers. Therefore, developing an ideal model that can accurately describe the nonlinearity of such device is crucial to control design. In this paper, the dynamic characteristics of a small-scale MR damper developed by our research group is tested, and the Stribeck effect is observed in the low velocity region. Then, an improved model based on sigmoid model is proposed to describe this Stribeck effect observed in the experiment. After that, the parameters of this model are identified by genetic algorithms, and the mathematical relationship between these parameters and the input current, excitation frequency and amplitude is regressed. Finally, the predicted forces of the proposed model are validated with the experimental data. The results show that this model can well predict the mechanical properties of the small-scale damper, especially the Stribeck effect in the low velocity region.